DEVELOPMENT OF CLUSTER POLICY OF FOREIGN COUNTRIES IN THE CONDITIONS OF THE GLOBAL COMPETITION - A. Akopyan (Вестник университета, 2019)
Real productivity of cluster policy in practice least of all corresponds to financial investments and expectations. So, many countries couldn't realize the expectations and hopes, trying to repeat success of the USA and having copied operating conditions and developments of their clusters. In the article the analysis of approaches of different foreign countries to realization of cluster policy is carried out.